Hypothermia and temperature modulation for intracerebral hemorrhage (ICH): pathophysiology and translational applications - Cadena, Angel J.; Rincon, Fred (Frontiers in Neuroscience, 2024)
Background: Intracerebral hemorrhage (ICH) still poses a substantial challenge in clinical medicine because of the high morbidity and mortality rate that characterizes it. This review article expands into the complex pathophysiological processes underlying primary and secondary neuronal death following ICH. It explores the potential of therapeutic hypothermia as an intervention to mitigate these devastating effects.Methods: a comprehensive literature review to gather relevant studies published between 2000 and 2023.Discussion: Primary brain injury results from mechanical damage caused by the hematoma, leading to increased intracranial pressure and subsequent structural disruption. Secondary brain injury encompasses a cascade of events, including inflammation, oxidative stress, blood-brain barrier breakdown, cytotoxicity, and neuronal death. Initial surgical trials failed to demonstrate significant benefits, prompting a shift towards molecular mechanisms driving secondary brain injury as potential therapeutic targets. With promising preclinical outcomes, hypothermia has garnered attention, but clinical trials have yet to establish its definitive effectiveness. Localized hypothermia strategies are gaining interest due to their potential to minimize systemic complications and improve outcomes. Ongoing and forthcoming clinical trials seek to clarify the role of hypothermia in ICH management.Therapeutic hypothermia offers a potential avenue for intervention by targeting the secondary injury mechanisms. The ongoing pursuit of optimized cooling protocols, localized cooling strategies, and rigorous clinical trials is crucial to unlocking the potential of hypothermia as a therapeutic tool for managing ICH and improving patient outcomes.